Microcontroller Based Traffic and Road Condition Monitoring Alert System Using Internet of Things - Jayasri, S; Karthika, D (International Journal of Computer Sciences and Engineering, 2025)
In later years ubiquity of private cars is getting urban movement more furthermore, more crowded. As result movement is becoming one of imperative issues in huge cities in all over the world. Some of the movement concerns are congestions furthermore, mischances which have caused a tremendous waste of time, property harm furthermore, ecological pollution. This research paper presents a novel insightful movement organization system, based on Web of Things, which is featured by low cost, high scalability, high compatibility, easy to upgrade, to replace conventional movement organization structure furthermore, the proposed structure can improve street movement tremendously. the high spectral efficiency and the resistance to multi-path fading, cooperative OFDMA becomes a hopeful contestant for high-speed wireless communication networks. The resource allocation in this paper is a mixed integer and continuous variable optimization problem, which is a NP hard problem. We construct a dynamic optimization framework for the RA problem, with the aim to maximize the average utility of all users with multi-service. Particle swarm optimization (PSO), as a population based stochastic optimization technique, is used to solve highly non-linear mixed integer optimization problems. PSO is used to solve the RA problem in OFDMA systems. In this paper, based on MDPSO, we propose a dynamic resource allocation algorithm to find the asymptotic optimal solution for the NP problem. Our proposed dynamic optimization framework for RA by considering three dynamic situations: time-varying fading channel, MSs states change, and relay stations (RSs) states change. The proposed dynamic algorithm achieves the better performance at linear complexity compared to the existing algorithms.